Convective carbon dioxide dissolution in a closed porous medium at high-pressure real-gas conditions. (August 2021) - Wen, Baole; Shi, Zhuofan; Jessen, Kristian; Hesse, Marc A.; Tsotsis, Theodore T.
Highlights: Convective CO 2 dissolution in closed porous media is modeled at reservoir conditions. The quasi-steady convective dissolution flux of CO 2 is measured by experiments. The models are validated by using both laboratory experiments and numerical simulations. The negative feedback of the pressure drop is weakened at real-gas conditions. The analysis provides a new direction determining the convective dissolution flux. Abstract: We combine modeling and measurements to investigate the dynamics of convective carbon dioxide (CO 2 ) dissolution in a pressure-volume-temperature cell, extending a recent study by Wen et al. ( J. Fluid Mech., vol. 854, 2018, pp. 56–87) at low-pressure under ideal-gas conditions to high-pressure and real-gas conditions. Pressure-dependent compressibility and solubility are included to model the evolution of CO 2 concentration in the gas phase and at the interface, respectively. Simple ordinary-differential-equation models are developed to capture the mean behavior of the convecting system at large Rayleigh number and are then verified by using both numerical simulations and laboratory experiments. The prefactor for the linear scaling of convective CO 2 dissolution is evaluated – for the first time – by using pressure-decay experiments in bead packs at reservoir conditions. The results show that our models could quantitatively predict the process of the convective CO 2 dissolution in pressure-decay experiments. Moreover, the results also reveal that for increasing gas pressure in closed systems, the negative feedback of the pressure drop – resulting from the dissolution of CO 2 in the liquid – is weakened due to the decrease of the solubility constant at real-gas conditions. Our analysis provides a new direction for determination and validation of the convective dissolution flux of CO 2 in porous media systems.